Research Status of Resource Utilization and Sulfidation Roasting Technology of a Low-grade Nickel Sulfide Ore - Yingying SHEN; Wenbo GUO; Yutian MA; Bingang LU; Tianyue LIU; Xianshao ZHAO (Kuangchan zonghe liyong)
The reserves of nickel ore resources are rich in China, mainly nickel sulfide.With the continuous exploitation of the high-grade nickel sulfide ore with high quality and easy to choose, its reserves and production are decreasing year by year. Therefore, the low-grade nickel sulfide ore with low nickel sulfide share, fine chimeric particle size and complex symbiosis will become the mainstream nickel resource in China. In this paper, the comprehensive treatment technology of the low-grade nickel sulfide ore is described in detail, and the existing treatment technology of the low grade nickel sulfide ore is introduced. Meanwhile, for the copper nickel sulfide lean ore of Jinchuan Company, the "step sulfidation roasting" process was put forward to, and the important significance of developing and studying the comprehensive treatment technology of the low-grade nickel sulfide ore is pointed out.